El pluralismo wittgensteiniano de Noë - Yuan, María Sol (2018)
This paper proposes a possible application of the enactive approach to Wittgenstein?s considerations regarding perception and its interpretative component, as it appears in his writings at the end of the 40s (especially in the second part of Philosophical Investigations), supposing for that purpose that the basic theses of the enactive approach of Alva Noë (2004) as well as the empirical cases used as evidence in their favor allow to analyze the relationship between ?sensory stimulus? and ?interpretation? arriving at conclusions compatible with those of Wittgenstein himself. It will be argued that it is possible to account for this basic form of understanding present in perceptions or visual experiences in conceptual terms, understanding them as a set of dynamic and adaptive skills, belonging primarily to the field of practice. Thinking part of the perceptual content in this way highlights the non-representational, non-empiricist aspects and the eminently practical resources that both positions rehearse on the subject. The limit of the amalgamation between the proposals of Wittgenstein and Noë will be indicated, on the other hand, in the highly communitarian component present in the epistemic and normative purpose of the Wittgensteinian philosophy.